THE EVOLVING ROLE OF HR IN ORGANIZATIONAL CHANGE MANAGEMENT - Karimova Mahbuba Sattor qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This study explores the shifting responsibilities and strategic importance of Human Resources (HR) in managing organizational change within the dynamic socio-economic landscape of Uzbekistan. As the country advances its market liberalization and digital modernization agenda under the “Uzbekistan 2030” reform strategy, HR functions are evolving from administrative support roles to change facilitation and transformation leadership. Using a mixed-methods approach—combining surveys of HR professionals, interviews with corporate leaders, and analysis of national reform documents—the study identifies emerging competencies, best practices, and challenges in HR-led change management. Findings indicate that strategic HR involvement significantly improves organizational agility, employee engagement, and the sustainability of reforms. Policy and practical recommendations are provided to enhance HR’s institutional capacity in Uzbekistan.